Sialic acid content of human low density lipoproteins affects their interaction with cell receptors and intracellular lipid accumulation. - Alexander N. Orekhov; V.V. Tertov; Igor A. Sobenin; Vladimir N. Smirnov; D P Via; Juan Guevara; AM Gotto; JD Morrisett (1992)
Low density lipoproteins (LDL) isolated from the plasma of patients with angiographically demonstrable coronary heart disease (CHD) induced accumulation of triglycerides, free cholesterol, and cholesteryl esters in cultured macrophages, smooth muscle cells, and endothelial cells derived from uninvolved intima of human aorta, but not in skin fibroblasts or hepatoma cells.The sialic acid content of LDL from CHD patients was 40-75% lower than that from healthy donors.There was a negative correlation between LDL sialic acid content and the LDL-induced accumulation of total intracellular cholesterol.Neuraminidase treatment of LDL from normal healthy donors produced sialic acid-depleted LDL (Ds-LDL) which was able to stimulate intracellular lipid accumulation.Neuraminidase treatment of LDL from CHD patients further increased its capacity to induce intracellular lipid accumulation.Sialic acid-poor LDL isolated by affinity chromatography of LDL from CHD patients induced a 2to 4-fold increase of free and esterified cholesterol in human intimal smooth muscle cells.Binding, uptake, and degradation of 1251-labeled Ds-LDL by macrophages and endothelial cells were 1.5-to 2-fold higher than for native LDL.Binding and uptake of Ds-LDL was inhibited 64-93% by the addition of 20-fold excess acetylated LDL (Ac-LDL); in the inverse experiment, the level of inhibition was 35-54%.These data indicate that a sialic acid-poor form of LDL isolated from CHD patients can interact with both native and scavenger LDL receptors.A sialic acid-poor form of LDL may be a naturally occurring ligand that interacts with the scavenger receptor(s) on macrophages and endothelial cells.-Orekhov, A.